A literature based critical analysis on the report population stabilization: The case for Pakistan - Jamal Abdul Nasir; M. H. Tahir (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2012)
Pakistan launched one of the first population control programs in the late 1950s, yet has lagged far behind other countries in effective implementation over the past five decades. The primary purpose of this note is to make a clear case for formulating an integrated and effective population policy in Pakistan. Therefore, this paper presents literature based demographic analysis on a recent report published by Ministry of Population Welfare: Population stabilization: the case for Pakistan (Khan 2010). The discussion presented in this paper should be viewed as the healthy criticism of the issue under debate. In addition, these comments are influenced by previous population research on Pakistan on the basis of the lessons which should be learnt from the previous population planning inputs. The paper presents the chapter by chapter analysis of the report and concludes that there is a weak relationship between family planning input and population policy in Pakistan.
Keywords: 330; Bevölkerungspolitik; Bevölkerungsentwicklung; Pakistan